UPAYA GERAKAN FRIDAYS FOR FUTURE (FFF) MENDUKUNG PARIS AGREEMENT DALAM KAMPANYE KESADARAN PERUBAHAN IKLIM DI SWEDIA - Sinaga, Enjellika; Takwa, Tuah Kalti (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
Climate change has become a global issue, affecting countries around the world, such as Sweden. There are adverse impacts that occur continuously due to climate change, so a social movement called Fridays For Future (FFF) emerged through a strike for the climate, the movement moves for climate change awareness action and demands policy makers to comply with the Paris Agreement. This research discusses how the efforts made by the FFF activist movement in dealing with climate change that occurred in Sweden. This research uses qualitative methods, data obtained from official websites, journals, books and interviews conducted with FFF activists. To analyze the data, the author uses Nelson Pichardo Almanzar's new social movement theory. The research shows how FFF responds to climate change in Sweden. FFF uses non-violent direct action in the form of climate strikes as its main strategy. In Sweden, FFF has succeeded in realizing the demands of encouraging the government to be aware of climate change through forming climate policies. Until now, FFF still continues to make efforts and improve strategies until its goals are achieved. Keywords: Fridays For Future (FFF), New Social Movement, Climate Change, Paris Agreement.